2021
DOI: 10.1002/pon.5789
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary validation of a questionnaire assessing psychological distress in caregivers of patients with malignant mesothelioma: Mesothelioma Psychological Distress Tool—Caregivers

Abstract: Objective: To develop a short, flexible, and comprehensive tool to measure psychological distress in caregivers of malignant mesothelioma (MM) patients: the Mesothelioma Psychological Distress Tool-Caregivers version (MPDT-C).Methods: Based on a systematic review of the relevant literature, aspects associated with caregiver distress were derived. Expert researchers/clinicians developed a pool of items for each identified aspect. Content validity was assessed through a multiple mixed-methods approach. A multice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Our results (i.e., the posterior of the present analysis) could become the prior distribution for future research developments, by gradually reducing the uncertainty on the final inference (Rupp et al, 2004). Moreover, they also emphasize the utility of adopting a trauma-focused framework for conceptualizing MM-related psychological pain, as already proposed in the literature (Hawley and Monk, 2004;Guglielmucci et al, 2014;Granieri, 2016;Di Basilio et al, 2021;Bonafede et al, 2022).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our results (i.e., the posterior of the present analysis) could become the prior distribution for future research developments, by gradually reducing the uncertainty on the final inference (Rupp et al, 2004). Moreover, they also emphasize the utility of adopting a trauma-focused framework for conceptualizing MM-related psychological pain, as already proposed in the literature (Hawley and Monk, 2004;Guglielmucci et al, 2014;Granieri, 2016;Di Basilio et al, 2021;Bonafede et al, 2022).…”
Section: Discussionsupporting
confidence: 66%
“…In-depth qualitative studies of the subjective experience of patients living with MM found that they felt ashamed, blamed, and stigmatized for their illness (Hughes and Arber, 2008;Borgogno et al, 2015;Franzoi et al, 2015;Granieri et al, 2017). Even decades after asbestos exposure, self-blaming and "an unpleasant feeling with accompanying beliefs that one should have thought, felt, or acted differently" (i.e., guilt) may persist (Borgogno et al, 2015;Guglielmucci et al, 2018a;Bonafede et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are cautionary notes on the use of default settings for convergence (Zitzmann & Hecht, 2019) or on the use of default prior distributions (Smid & Winter, 2020). Nevertheless, Bayesian factor analysis (BFA) is meanwhile regularly used (e.g., Bonafede et al, 2021; Wang et al, 2021; Weide et al, 2021). It follows from the regular use of BFA that plausible values as factor score estimates computed from BFA (Asparouhov & Muthén, 2010a, 2010b) may also be used regularly.…”
mentioning
confidence: 99%
“…Bayesian structural equation modeling (BSEM) has been proposed by Muthén and Asparouhov (2012) as an alternative to conventional structural equation modeling and several improvements of BSEM have meanwhile been proposed and realized (Asparouhov & Muthén, 2021;Asparouhov, Muthén, & Morin, 2015;Zitzmann & Hecht, 2019). Advantages of BSEM are that it can be performed with relatively small samples (Bonafede, Chiorri, Azzolina, 2021) and that priors for the variability of loadings can be specified. BSEM thereby allows to overcome problems of specifying fixed zero loadings in the independent clusters model (Beauducel & Hilger, 2020) and it also allows for the specification of complex loading patterns as, for example, circumplex models (Weide, Scheuble, & Beauducel, 2021).…”
Section: The Validity Of Mean Plausible Valuesmentioning
confidence: 99%